The Prevalence of Rectovaginal Colonization and Antibiotic Susceptibility Pattern of Streptococcus agalactiae in Pregnant Women in Al-Zahra Hospital, Rasht, Iran. Issue 3 (May 2019) - Sahraee, Shokoufeh; Milani, Forozan; Atrkar Roushan, Zahra; Hedayati Ch, Mojtaba; Rostami, Soodabeh; Shoja, Saeed; Sheikhi, Raheleh
Abstract : Background: Maternal rectovaginal colonization with group B streptococcus (GBS) is a main risk factor for vertical transmission of GBS to newborns and life-threatening neonatal invasive diseases. The aim of this study was investigation of the prevalence of anorectal and vaginal colonization with GBS in late of pregnancy by culture-based and polymerase chain reaction (PCR) methods and antimicrobial susceptibility patterns of the GBS isolates in Rasht, Iran. Methods: We analyzed 245 anorectal and vaginal swab samples separately from pregnant women at 35 to 37 weeks of gestation. All samples were cultured after enrichment in a selective Todd-Hewitt broth and then assayed by phenotypic characterizations and PCR method for cfb conserved gene. Antimicrobial susceptibility was performed using the Kirby–Bauer method. Results: In total of 245 vaginal samples, 19 (7.8%) were positive based on culture method and 28 (11.4%) by PCR method. Among 245 rectal samples, 24 (9.8%) were positive by culture and 29 (11.8%) samples were positive by PCR. Of 245 pregnant women studied were found to have 9.7% GBS rectovaginal by culture and 15.9% by PCR methods. All GBS isolates were sensitive to ampicillin (77.2%) and vancomycin (72.2%) and were resistant to Penicillin (88.6%), ceftriaxone (75%), clindamycin (95.4%), azithromycin (86.3%), tetracycline (61.3%), erythromycin (47.7%), and levofloxacin (27.2%). Conclusions: The results of this study indicate that the frequency of GBS isolation from rectal samples was higher than vaginal samples by both culture and PCR. Our study recommended intrapartum antibiotic prophylaxis against GBS infections based on ampicillin or vancomycin for GBS carriers in Rasht.